2008
DOI: 10.1002/ibd.20524
|View full text |Cite
|
Sign up to set email alerts
|

Tetomilast suppressed production of proinflammatory cytokines from human monocytes and ameliorated chronic colitis in IL-10-deficient mice

Abstract: Tetomilast exerts its antiinflammatory effects on human monocytes and CD4 cells. Combined with in vivo data these findings support the feasibility of tetomilast as a novel drug for inflammatory bowel diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…18) Moreover, it has been reported that tetmilast (10 mg/kg) suppressed cytokine production in a murine chronic colitis model. 20) Therefore, we decided the dose of tetomilast as 10 mg/kg in the present study. The rabbits were divided into three groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18) Moreover, it has been reported that tetmilast (10 mg/kg) suppressed cytokine production in a murine chronic colitis model. 20) Therefore, we decided the dose of tetomilast as 10 mg/kg in the present study. The rabbits were divided into three groups.…”
Section: Methodsmentioning
confidence: 99%
“…16) Tetomilast also attenuates acute lung injury, 17,18) and its anti-inflammatory effects have been noted in both the liver 19) and colon. 20) In the present study, we determine whether tetomilast could be an effective treatment for PPE-induced emphysema in rabbits.…”
Section: Tetomilast Attenuates Elastase-induced Pulmonary Emphysema Tmentioning
confidence: 95%
See 1 more Smart Citation
“…29,30 Tetomilast (OPC-6535), originally developed to inhibit superoxide production, suppressed TNF-α and IL-12 but not IL-10 production from LPS-stimulated human monocytes and ameliorated chronic colitis in IL-10 −/− mice. 31 Histidine inhibited LPS-induced TNF-α and IL-6 production by mouse macrophages and dietary histidine ameliorated colitis in a IL-10 −/− mouse transfer colitis model. 32 Interestingly, amino acid profiling revealed decreased levels of plasma histidine concentration in the patients with active Crohn' s disease.…”
Section: Conditioning and Control Of Differentiation Of Innate Immunementioning
confidence: 97%
“…In preclinical studies it has been shown to inhibit the release of proteases, superoxide anions, and other functions attributable to activated human leukocytes [63]. Although its mode of action has not been completely understood, when tested on mouse or rat models of colitis and, in vitro, on human immune cells, it suppressed LPS-induced production of TNF-α and IL-12 in monocytes, and both TNF-α and INF-γ in CD4-positive T cells, leading to reduced colonic damages [64]. …”
Section: Pde4 Inhibitors In Preclinical Studies Of Ibdmentioning
confidence: 99%